Bibliometric Analysis of Forensic Accounting and Fraud Detection Research Trends - Judijanto, Loso; Rahman, Kristanti; Sudarmanto, Eko; Khikmah, Siti Noor; Bakri, Asri Ady (Westscience Press, 2025)
Forensic accounting and fraud detection have become increasingly critical in mitigating financial crimes and ensuring corporate transparency. This study conducts a bibliometric analysis to explore the research trends, key contributors, and emerging themes in forensic accounting and fraud detection. Using data exclusively from the Scopus database and analyzed through VOSviewer, the study identifies influential publications, prominent authors, and evolving research directions. The findings indicate a shift from traditional forensic accounting methods to technology-driven approaches, such as big data analytics, artificial intelligence, and blockchain. The co-authorship analysis highlights significant international collaborations, particularly among scholars in the Middle East and Europe. Despite these advancements, challenges remain, including regulatory inconsistencies and the need for standardized forensic accounting frameworks. This study contributes to the literature by providing a structured overview of forensic accounting research trends and offering insights for academics, practitioners, and policymakers to enhance fraud prevention strategies and financial accountability.